Effect of active static stretching on glycemia in type 2 diabetes - Nascimento Folha, Pablo; P. F. Bacurau, Reury; S. Aoki, Marcelo; Massa, Marcelo (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Type 2 diabetes Mellitus (T2DM) is a chronic disease whose prevalence is increasing worldwide. It is characterized by insulin resistance in insulin-dependent tissues (e.g. skeletal muscle, adipose tissue). Despite new evidence that stretching may aid in glycemic control, this form of physical exercise remains underutilized in the therapy of T2DM. Objective: The objective of this study was to evaluate the effects of active static stretching on the glycemia of individuals with T2DM. Methods: Twenty-nine volunteers participated in the study, divided into 3 randomly assigned groups: 30-second stretching group (GA30) with 10 participants; 45-second stretching group (GA45) with 10 participants; control group (CG) with 9 participants. Results: Analysis of the intervention groups versus the control group showed that the intervention groups GA30 and GA45 had a significant milligrams per deciliter (mg/dl) reduction in glycemia compared to the control group (control Δ-7.9mg/dl, GA30 Δ12.7mg/dl and GA45 Δ18.5mg/dl >0.001) and between intervention groups (GA30 and control Δ 20.5mg/dl, P 0.002), GA45 and control (Δ 26.4mg/dl, P 0.001). There was no difference between the intervention groups. The results suggest that, regardless of the application time, active static stretching reduces glycemia in individuals with T2DM. In an analysis divided into 4 stages (1st and 2nd weeks, 3rd and 4th weeks, 5th and 6th weeks, and 7th and 8th weeks), the results obtained from the glycemic difference before and after each two weeks were as follows: GA30 pre and post (1st ≠ 17.4 mg/dl, 2nd ≠ 5.8 mg/dl, 3rd ≠ 14.5 mg/dl, and 4th ≠ 8.9 mg/dl), GA45 pre and post (1st ≠ 18.1 mg/dl, 2nd ≠ 17.0 mg/dl, 3rd ≠ 19.2 mg/dl, and 4th ≠ 20.0 mg/dl), and CG pre and post (1st ≠ -10.4 mg/dl, 2nd ≠ -3.7 mg/dl, 3rd ≠ -11.4 mg/dl, and 4th ≠ -11.7 mg/dl). Conclusion: This interaction between the two-factor period (Group and Period) did not have a significant effect. Finally, a descriptive analysis of pre- and post-intervention glucose behavior showed the variability of glycemia during the period. Thus, active static stretching significantly reduces acute and chronic glycemia in individuals with T2DM compared to control.